2022
DOI: 10.1142/s0219877023500049
|View full text |Cite
|
Sign up to set email alerts
|

Okay Google, Good to Talk to You… Examining the Determinants Affecting Users’ Behavioral Intention for Adopting Voice Assistants: Does Technology Self-Efficacy Matter?

Abstract: This study investigates the impact of attitude and trust on the behavioral intention of adopting artificial intelligence (AI)-based voice-assistant services through the integration of parasocial relationship theory (PSR) and human–computer interaction (HCI) theory. Employing a deductive approach, partial least squares structural equation modeling (PLS-SEM) was performed to assess the proposed model based on 295 participants by using a purposive sampling method. Findings revealed that the functional components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…The influence of parasocial interaction on IPA usage intensity (H4) was strongly supported in this study, with a significant coefficient ( β = 0.511, p < 0.001). This result corroborates earlier research that suggests a robust link between the development of parasocial relationships and increased interaction with technology 104 , 105 . The substantial coefficient indicates that users who develop a sense of friendship or emotional connection with their IPAs tend to use these systems more extensively.…”
Section: Discussionsupporting
confidence: 92%
“…The influence of parasocial interaction on IPA usage intensity (H4) was strongly supported in this study, with a significant coefficient ( β = 0.511, p < 0.001). This result corroborates earlier research that suggests a robust link between the development of parasocial relationships and increased interaction with technology 104 , 105 . The substantial coefficient indicates that users who develop a sense of friendship or emotional connection with their IPAs tend to use these systems more extensively.…”
Section: Discussionsupporting
confidence: 92%
“…Scholars are increasingly interested in assessing consumer value perceptions and the overall effects on behavior. A number of empirical studies confirm that perceived value influences customers' attitudes and behavior (Gordon et al, 2018;Ashrafi and Easmin, 2022;Roh et al, 2022). For example, Ashrafi et al (2021) found that a customer's value perceptions of an offering's worth influence their intention to use services.…”
Section: Perceived Valuementioning
confidence: 95%
“…Previous studies have investigated the association between attitude and adoption intention toward novel technologies (Ashrafi et al, 2021;McLean et al, 2020;Siahaan et al, 2022). In this vein, recent studies on adoption of AI-based technologies suggest attitude is crucial for understanding individuals' adoption intentions (Ashrafi and Easmin, 2022;Dwivedi and Wang, 2022). For instance, in the airline industry, Feng et al (2018) found that customers view artificial intelligence-based technology as a risk to their autonomy, leading to the formation of a negative attitude toward adopting such technology.…”
Section: Attitude Toward Aimentioning
confidence: 99%
“…Davis (1989) defined perceived ease of use as “the degree to which a person believes that using a particular system would be free of effort” (p. 320). Perceived ease of use generally reflects the degree to which the usage of the technological system is uncomplicated from the user’s perspective to use it without putting much effort (Ashrafi and Easmin, 2023). In the context of the online platform, perceived ease of use indicates the extent of consumers' belief about using the apps with applying minimal effort (Ismagilova et al ., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%